The Effects of Product Quality, Price, and Product Design on Purchasing Decisions (Study on Electric Motorcycle Owners in Purwokerto) - Alfalisyado; Totok Haryanto (Universitas Muhammadiyah Palu, 2023)
This study analyzes the effect of product quality, price, and design on purchasing decisions. The approach used in this research is quantitative. To obtain data from respondents, researchers used purposive random sampling technique. The roscoe approach was used in this study. The questionnaire was distributed to 100 respondents. The analysis used by researchers is multiple linear regression analysis using SPSS version 25. The results of this study are product quality, price, and product design partially have a positive and significant effect on purchasing decisions. t-statistic of product quality is 2.449 and a significance value of 0.016. in addition, t-statistic of price is 3.963 with significance value 0.000. lastly t-statistic of product design is 2.276 with a significance value 0.025.